A Psychometric Study of a Spanish Version of the Negative Acts Questionnaire-Revised: Confirmatory Factor Analysis - Dujo López, Víctor; González Trijueque, David; Graña Gómez, José L.; Andreu Rodríguez, José M. (Frontiers in Psychology, 2020)
Background The NAQ (Negative Acts Questionnaire) has been widely used in more than 40 countries to measure the mobbing phenomenon. This research aims to present a psychometric study based on the Spanish version of the NAQ-R carried out by González-Trijueque and Graña (2013). As opposed to the original scale, this sample contains 23 items and a three-dimension model (personal bullying, work-related bullying, and physically intimidating forms of bullying). Methods We used a heterogeneous occupational sample of 2,538 Spanish employees to analyze internal consistency and concurrent validity. In addition, a Confirmatory Factor Analysis was carried out based on the GLS (generalized least squares) method. Results Results showed high internal reliability (Cronbach’s alpha = 0.91) and high correlations containing clinical symptoms, burn-out indicators, and coping resources. The Confirmatory Factor Analysis developed upon the heterogeneous occupational sample validates the three-dimension structure in the Spanish version of the NAQ-R aimed to measure harassment behaviors at the workplace. Conclusion The NAQ-R reaffirms its validity and reliability as a measure for mobbing-related behaviors. Hence, the scale may become a useful tool in research and forensic practice.